Method for plating gold, palladium and nickel on connector terminal
Through weak acid activation and pulse current plating technology, gold-palladium-nickel alloy layer is formed, and molybdenum, tungsten and graphene are introduced, solving the problems of poor adhesion and insufficient corrosion resistance of traditional plating in extreme environments, and achieving the improvement of high bond strength, corrosion resistance and mechanical properties of the plating.
Patent Information
- Application Number
- CN202411974919.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional single metal coatings have poor adhesion and insufficient corrosion resistance in extreme environments such as high temperature and high humidity, and are prone to cracks or peeling due to thermal expansion and contraction, which limits their application in high-performance electronic components.
Weak acid activation in pretreatment combined with pulse current plating technology, by cleaning and activating the terminal surface, the uniform deposition and grain refinement of metal ions are controlled by using the pulse current method to form a gold-palladium-nickel alloy layer, and molybdenum, tungsten trace elements and graphene-enhanced nanoparticles are introduced into the electroplating solution.
It significantly improves the bonding strength between the plating and the substrate, enhances the corrosion resistance, hardness and wear resistance of the plating, and ensures long-term service stability and high-performance applications of the connector terminals.
Smart Images

Figure CN119736678A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal surface treatment, in particular to a method for gold-palladium-nickel plating of connector terminals. Background Art
[0002] In the field of electronic component manufacturing, connector terminals are key components, and their performance directly affects the electrical connection stability and long-term reliability of the equipment. Traditionally, the terminal surface is mostly protected and conductively treated with a single metal plating (such as gold, silver or nickel). However, the adhesion of this type of coating is poor, especially in extreme environments such as high temperature and high humidity. It is easy to cause cracks or peeling due to thermal expansion and contraction, which significantly affects the bonding strength between the terminal and the substrate. At the same time, the traditional single metal plating has insufficient corrosion resistance and is prone to oxidation or corrosion in harsh environments, resulting in increased contact resistance, which ultimately affects the signal transmission quality and equipment performance.
[0003] In recent years, in order to improve the performance of coatings, multi-element co-deposition technology has gradually attracted attention. By depositing a composite coating of multiple metal elements, the adhesion and corrosion resistance of traditional single metal coatings can be improved to a certain extent, and its ability to adapt to complex environments can be enhanced. However, the practical application of multi-element co-deposition technology still faces many technical bottlenecks. Especially in terms of plating solution composition control and process parameter regulation, the existing technology is difficult to achieve uniform deposition and grain refinement of metal ions, resulting in insufficient coating adhesion and unstable performance. In addition, the coating is prone to peeling due to the accumulation of defects during long-term service, which limits its application in high-performance electronic components.
[0004] Some studies have proposed that the hardness and wear resistance of the coating can be significantly improved by replacing or supplementing a single metal coating with precious metals (such as palladium and platinum). However, the high cost of precious metals makes it difficult to promote this solution in actual production, and simply relying on the addition of precious metals cannot fundamentally solve the problem of insufficient adhesion of the coating in extreme environments. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a method for gold-palladium-nickel plating of connector terminals, which solves the problems of poor adhesion, insufficient corrosion resistance, and easy cracking or peeling due to thermal expansion and contraction of traditional single metal plating, while overcoming the problem of difficulty in controlling the composition of the plating solution and the uniformity of deposition in the multi-element co-deposition process in the prior art.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: A method for plating gold-palladium-nickel on connector terminals, comprising the following steps: Pretreatment: Clean the connector terminals to be plated to remove grease, dirt and oxide layer, and then activate them by soaking in a weak acid solution to prepare the terminal surface for subsequent deposition; The cleaning process is achieved through ultrasonic technology, which has high efficiency in removing oil and oxide layers. The ultrasonic frequency (60-80kHz) cleans the surface through micro-bubble explosion and can penetrate into tiny surface depressions. The cleaning time (3-10min) and temperature (50-60℃) settings can effectively soften and decompose pollutants. The ultrasonic power density (1-2W / cm 2 ) ensures that the cleaning force is moderate and does not damage the substrate.
[0007] Soaking in weak acid solution (such as citric acid, oxalic acid, phosphoric acid or boric acid) can further remove the stubborn oxide layer. Weak acid can react slightly with oxide to form soluble salt. Controlling the soaking time (1 to 3 minutes) avoids excessive corrosion while maintaining the activity of the metal surface. Immediately clean and dry after soaking to avoid re-oxidation or contamination of the surface.
[0008] Preparing an electroplating solution: preparing an electroplating solution for generating an alloy phase; Gold, palladium and nickel are the main components to form an alloy phase, in which gold provides excellent corrosion resistance and conductivity, palladium increases hardness and wear resistance, and nickel enhances the mechanical properties and toughness of the coating. The setting of the molar ratio ensures uniform composition of the alloy phase and optimizes its physical and chemical properties. Molybdenum and tungsten are trace elements that further improve wear resistance and oxidation resistance through alloying, while refining the grain structure of the coating, thereby enhancing the mechanical properties and surface quality of the coating.
[0009] Pulse current plating: The pulse current method is used to precipitate metal ions in the plating solution and deposit them on the surface of the connector terminal to form an alloy layer; Pulse current electroplating promotes uniform deposition of metal ions through periodically changing current density. The setting of the positive and negative half-cycle current ratio reduces the unevenness of anode dissolution and effectively inhibits the generation of grain boundary defects during electroplating. The selection of the frequency range (55-65Hz) optimizes the diffusion rate and deposition rate of metal ions, making the alloy coating dense and uniform, and the grain structure refined, thereby improving the hardness and wear resistance of the coating.
[0010] Electroplating process control: Inhibitors are added during the electroplating process to adjust the pH value and temperature of the plating solution and inhibit the adsorption of impurities; Potassium fluoroborate as an inhibitor can effectively reduce the impurity deposition formed by metal ions during the deposition process, thereby improving the purity and smoothness of the coating. At the same time, by maintaining the buffer pH value in the range of 3.5±0.1, it can prevent uneven precipitation caused by changes in the acidity and alkalinity of the plating solution and ensure the stable deposition of metal ions. Temperature control helps to balance the diffusion of metal ions and the chemical reaction rate, further optimizing the quality of the coating.
[0011] Post-processing: After electroplating, the coating is cleaned and dried, and the appearance quality and various performance indicators of the finished product are checked to ensure that they meet the standards.
[0012] Post-treatment cleaning can completely remove the plating solution or impurities that may remain during the electroplating process to avoid secondary contamination; the drying step prevents the plating layer from generating micro cracks due to rapid drying through appropriate temperature control (such as hot air below 60°C). In addition, post-treatment also includes testing of performance indicators such as thickness, smoothness, and hardness of the plating layer to ensure that it meets application requirements.
[0013] Preferably, the cleaning adopts ultrasonic cleaning technology to remove dirt, and the ultrasonic frequency is 60-80kHz, the cleaning time is 3-10min, the cleaning liquid temperature is 50-60℃, and the ultrasonic power density is 1-2W / cm 2 .
[0014] Preferably, the weak acid solution includes one or more of the following: citric acid solution, oxalic acid solution, phosphoric acid solution and boric acid solution. The soaking time is 1 to 3 minutes, and the surface is immediately cleaned and dried after the soaking.
[0015] Preferably, in the electroplating solution, the molar ratio of gold, palladium and nickel is 0.9-1.1:0.3-0.6:1.8-2.2, and the molar ratio of molybdenum to tungsten is 0.05-0.15:0.85-0.95.
[0016] Preferably, in the pulse current electroplating, a periodic inversion pulse power supply mode is adopted, and the positive and negative half-cycle current ratio is 0.9-1.1:2.8-3.2, and the frequency is 55-65 Hz.
[0017] Preferably, the inhibitor is potassium fluoroborate, and the pH is maintained in the range of 3.5±0.1.
[0018] Preferably, the electroplating time is maintained at 45 to 60 minutes, and during electroplating, the temperature of the electroplating solution is maintained at 55 to 60°C.
[0019] Preferably, graphene-enhanced nanoparticles are further added to the electroplating solution, and the graphene-enhanced nanoparticles are prepared by a sol-gel method. The precursor containing graphene sheets prepared by the sol-gel method is mixed with gold, palladium and nickel electroplating solutions to form an enhanced coating.
[0020] As an enhanced nanoparticle, graphene has extremely high conductivity, mechanical strength and corrosion resistance. The precursor prepared by the sol-gel method can be evenly dispersed in the electroplating solution to avoid particle agglomeration affecting the quality of the coating. The addition of graphene can effectively improve the conductivity of the coating (because its two-dimensional structure provides electron channels), wear resistance (because of its high hardness) and corrosion resistance (because its barrier effect blocks the intrusion of corrosive media). This enhanced coating exhibits excellent performance in extreme environments and is suitable for aerospace, deep-sea exploration and other fields.
[0021] The present invention provides a method for plating gold-palladium-nickel on connector terminals. It has the following beneficial effects: 1. The present invention adopts the technical solution of weak acid activation combined with pulse current electroplating in pretreatment, removes grease, dirt and oxide layer by cleaning and activating the terminal surface, improves the activity of the substrate surface by immersion in weak acid solution, and uses pulse current method to control the uniform deposition and grain refinement of metal ions, significantly improving the bonding strength between the coating and the substrate. Compared with the existing technology that relies solely on static DC current electroplating, the coating has poor adhesion and is prone to cracking or peeling due to thermal expansion and contraction. Therefore, the present invention effectively solves the technical bottleneck of insufficient adhesion and ensures the stability of the electrical performance of the connector terminal under long-term service.
[0022] 2. The present invention forms a composite coating with stronger corrosion resistance by introducing trace elements of molybdenum and tungsten and graphene-enhanced nanoparticles into the electroplating solution; at the same time, potassium fluoroborate inhibitor is used to dynamically adjust the pH value during the electroplating process, further improving the compactness and corrosion resistance of the coating. Compared with the problem of shortened life of a single metal coating due to the invasion of corrosive media in the prior art, the technical solution of the present invention effectively enhances the ability of the coating to resist erosion from the external environment, significantly prolongs its service life, and reduces the frequency and cost of equipment maintenance.
[0023] 3. By adopting the pulse current method and precisely controlled electroplating process parameters (such as the positive and negative half-cycle current ratio and frequency) combined with the optimized design of trace elements, the grain structure of the coating is improved, making its surface smoother and flatter, and presenting a uniform and bright color. At the same time, the surface smoothness and optical quality of the coating are further improved by the addition of graphene nanoparticles. Compared with the problems of difficult assembly operations and poor visual recognition caused by rough surfaces in the prior art, the technical solution of the present invention not only improves the appearance quality of the connector terminals, but also promotes higher-precision assembly operations and enhances the overall competitiveness of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The present invention is a flow chart of the electroplating method. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] In order to better understand the present invention, the above contents are described in detail below in conjunction with specific embodiments. Please refer to the attached Figure 1 Example 1: Basic gold-palladium-nickel plating process Specific steps and parameters: Preprocessing: Ultrasonic cleaning technology was used, with an ultrasonic frequency of 65kHz, a cleaning liquid temperature of 55°C, a cleaning time of 8 minutes, and an ultrasonic power density of 1.5W / cm 2 ; After cleaning, the terminals were immersed in a 1% oxalic acid solution for 2 minutes, and then washed with deionized water and dried.
[0027] Electroplating solution configuration: An electroplating solution containing gold, palladium and nickel ions was prepared in a molar ratio of 1.0:0.5:2.0, and the pH value of the plating solution was controlled at 3.5.
[0028] Electroplating process: Use DC power supply for electroplating, current density 0.5A / dm 2 The plating time was 60 minutes and the plating solution temperature was maintained at 55°C.
[0029] Effect and summary: The gold-palladium-nickel composite coating with an average thickness of about 5 μm was obtained. The coating surface was uniform and dense. X-ray diffraction analysis confirmed that the alloy phase composition was in line with expectations, and the microhardness was measured to be HV200. The coating showed good electrical properties and corrosion resistance, but there was still room for improvement in surface hardness and wear resistance.
[0030] analyze: This example is a basic process, and the focus is on verifying the basic forming effect and performance of the gold-palladium-nickel alloy coating. Since no alloying elements are added, the coating hardness is low and the surface roughness needs to be further improved.
[0031] Example 2: Process for enhancing hardness by alloying elements Specific steps and parameters: Pretreatment and plating solution configuration: The pretreatment steps are consistent with those in Example 1.
[0032] An electroplating solution containing gold, palladium and nickel ions in a molar ratio of 1.0:0.5:2.0 was prepared, and 0.1% of molybdenum salt was added as an alloying element. The pH value of the plating solution was controlled at 3.5.
[0033] Electroplating process: Use DC power supply for electroplating, current density 0.5A / dm 2 The plating time was 60 minutes and the plating solution temperature was maintained at 55°C.
[0034] Effect and summary: Through the microhardness test, the hardness of the coating increased from HV200 to HV250, the surface wear resistance was significantly enhanced, and other properties (such as thickness and uniformity) were consistent with Example 1. This result confirms that the addition of trace molybdenum salt significantly improves the mechanical properties of the coating by refining the grains and strengthening the alloy phase.
[0035] analyze: Compared with Example 1, the addition of molybdenum salt as an alloying element significantly improves the hardness of the coating. Molybdenum optimizes the microstructure of the coating through alloying, forms a more uniform grain distribution, and improves the wear resistance of the coating. However, the addition of molybdenum has limited effect on surface roughness and smoothness, which needs further optimization.
[0036] Example 3: Pulsed current process for optimizing surface roughness Specific steps and parameters: Pretreatment and plating solution configuration: The pretreatment steps are consistent with those in Example 1.
[0037] An electroplating solution containing gold, palladium and nickel ions was prepared in a molar ratio of 1.0:0.5:2.0, and the pH value of the plating solution was maintained at 3.5±0.1.
[0038] Electroplating process: Adopting periodic inversion pulse power supply, the positive and negative half-cycle current ratio is 1:3, the frequency is 60Hz, and the current density is 0.7A / dm 2 , electroplating time 45 minutes, electroplating solution temperature 55℃.
[0039] Effect and summary: The surface roughness Ra of the coating is reduced to 0.05μm, the microhardness is increased to HV280, the coating surface is smooth and has a bright metallic luster, which is significantly improved compared to the rough surface and low hardness of DC plating. This process successfully optimizes the surface quality and mechanical properties of the coating.
[0040] analyze: Compared with Example 1 and Example 2, the pulse current method further refines the coating grains, reduces grain boundary defects, and improves surface roughness. Precise control of the positive and negative half-cycle current ratio and frequency is the key to improving surface quality and hardness, but this method has little effect on coating thickness.
[0041] Example 4: Improving coating density and gloss by stabilizing pH value Specific steps and parameters: Pretreatment and plating solution configuration: The pretreatment steps are consistent with those in Example 1.
[0042] Potassium fluoroborate was added to the electroplating solution as an inhibitor, and the pH value was dynamically adjusted to maintain at 3.5±0.1.
[0043] Electroplating process: Use DC power supply, current density 0.5A / dm 2 , electroplating time 60 minutes, electroplating solution temperature 55℃.
[0044] Effect and summary: The density of the coating was significantly improved, the surface gloss reached the mirror level, and the corrosion resistance was also improved. This result shows that a stable pH value can effectively improve the deposition rate and uniformity of metal ions, thereby optimizing the structure and appearance of the coating.
[0045] analyze: Compared with Example 2, the addition of the inhibitor significantly improved the surface gloss and density of the coating. The dynamic regulation of the potassium fluoroborate inhibitor effectively inhibited the deposition of impurities in the plating solution and reduced the formation of rough surfaces, but the effect on improving the hardness was not as good as that of the addition of molybdenum salts.
[0046] Example 5: Realization of graphene-enhanced composite coating Specific steps and parameters: Pretreatment and graphene precursor preparation: The pretreatment steps are consistent with those in Example 1.
[0047] A precursor solution containing graphene sheets was prepared using a sol-gel method, with a graphene concentration of 0.1 wt%.
[0048] Electroplating solution configuration and process: Prepare an electroplating solution containing gold, palladium and nickel (molar ratio of 1.0:0.5:2.0), add the graphene precursor solution, and stir evenly to ensure that the graphene is evenly dispersed.
[0049] Electroplating uses a periodic inversion pulse power supply with a positive and negative half-cycle current ratio of 1:3, a frequency of 65Hz, and a current density of 0.7A / dm 2, electroplating time 45 minutes, electroplating solution temperature 55℃.
[0050] Effect and summary: The coating thickness is slightly reduced to 4.5 μm, but the elastic modulus E is increased to 20 GPa, the fracture toughness KIC is 12 MPa·√m, and the conductivity is increased to 2.3×10 7 S / m. This enhanced coating exhibits excellent performance in terms of wear resistance, electrical conductivity and corrosion resistance.
[0051] analyze: Compared with Example 3 and Example 4, the addition of graphene further enhances the mechanical and electrical properties of the coating. As a two-dimensional material, graphene forms a strong network structure in the coating, greatly improving the strength and conductivity of the coating, but since the doped particles affect the thickness and deposition uniformity of the coating, the doping amount needs to be controlled to balance the performance.
[0052] Example 6: Effect of graphene doping concentration on electrical properties Specific steps and parameters: Pretreatment and graphene precursor preparation: The pretreatment steps are consistent with Example 5, including using an ultrasonic cleaning device (65kHz frequency, 55°C cleaning liquid temperature, cleaning time 8 minutes) to clean the connector terminals and using a 1% oxalic acid solution for activation (immersion for 2 minutes).
[0053] The graphene precursor was prepared by a sol-gel method, and the concentration was adjusted to 0.2 wt % to ensure that a higher content of graphene could be evenly dispersed in the plating solution.
[0054] Electroplating solution configuration and process: An electroplating solution containing gold, palladium and nickel (molar ratio of 1.0:0.5:2.0) was prepared, 0.2 wt % of graphene precursor was added, and a stirrer was used to stir at a constant temperature (55° C.) for 20 minutes to ensure that the graphene was evenly dispersed.
[0055] During the electroplating process, a periodic inversion pulse power supply is used, with a positive and negative half-cycle current ratio of 1:3, a frequency of 65Hz, and a current density of 0.7A / dm 2 The plating time was 45 minutes and the plating solution temperature was maintained at 55°C.
[0056] Effect: Through experimental measurement, the room temperature conductivity of the coating increased from 2.3×10 7 S / m is further increased to 2.5×10 7S / m, showing higher conductivity. In addition, the coating surface still maintains good uniformity and integrity, but the thickness is slightly reduced to 4.4μm. Analysis shows that the increase in graphene doping concentration promotes the enhancement of the recombination effect and significantly improves the transmission efficiency of electrons in the coating.
[0057] Summary of embodiments: In this embodiment, the conductivity of the coating is further improved by increasing the graphene concentration to 0.2wt%. The two-dimensional structure of graphene can provide an efficient electron transmission channel, and the increase in its content forms a denser conductive network, thereby increasing the conductivity by about 8.7% (from 2.3×10 7 S / m to 2.5×10S / m). At the same time, the higher concentration of graphene did not significantly affect the uniformity of the coating surface, showing good deposition stability.
[0058] Comparative Example 1 (corresponding to Example 1: basic gold-palladium-nickel plating process) Difference and process: Preprocessing stage: The conventional chemical cleaning process was changed to a conventional degreasing agent, and ultrasonic cleaning was not used; the degreasing agent concentration was 2%, the cleaning time was 10 minutes, and the cleaning temperature was 40°C. The oxalic acid activation step remained unchanged.
[0059] Electroplating solution configuration: An electroplating solution of gold, palladium and nickel ions was prepared in a molar ratio of 1.0:0.5:2.0, and the pH value was controlled at 3.5.
[0060] Electroplating process: Use DC power supply, current density 0.5A / dm 2 The plating time was 60 minutes and the plating solution temperature was maintained at 55°C.
[0061] Comparative Example 2 (corresponding to Example 2: Process for enhancing hardness by alloying elements) Difference and process: Preprocessing stage: The same ultrasonic cleaning and oxalic acid activation process as in Example 1 was adopted.
[0062] Electroplating solution configuration: The electroplating solution is prepared with gold, palladium and nickel ions in a molar ratio of 1.0:0.5:2.0, and no alloying elements such as molybdenum salts are added.
[0063] Electroplating process: Use DC power supply for electroplating, current density 0.5A / dm 2 The plating time was 60 minutes and the plating solution temperature was maintained at 55°C.
[0064] Comparative Example 3 (corresponding to Example 3: Pulse current process for optimizing surface roughness) Difference and process: Preprocessing stage: The same ultrasonic cleaning and oxalic acid activation process as in Example 1 was adopted.
[0065] Electroplating solution configuration: The electroplating solution of gold, palladium and nickel ions was prepared in a molar ratio of 1.0:0.5:2.0, and the pH value was maintained at 3.5±0.1.
[0066] Electroplating process: Using conventional DC power supply instead of periodic inversion pulse power supply, the current density is 0.7A / dm 2 The plating time was 45 minutes and the plating solution temperature was maintained at 55°C.
[0067] Comparative Example 4 (corresponding to Example 4: Improving the density and gloss of the coating by stabilizing the pH value) Difference and process: Preprocessing stage: The same ultrasonic cleaning and oxalic acid activation process as in Example 1 was adopted.
[0068] Electroplating solution configuration: The electroplating solution of gold, palladium and nickel ions was prepared in a molar ratio of 1.0:0.5:2.0, and the pH value was controlled at 4.0 (under unstable conditions). Potassium fluoroborate was not added as an inhibitor.
[0069] Electroplating process: Use DC power supply for electroplating, current density 0.5A / dm 2 The plating time was 60 minutes and the plating solution temperature was maintained at 55°C.
[0070] Comparative Example 5 (Corresponding to Example 5: Implementation of Graphene Enhanced Composite Coating) Difference and process: Preprocessing stage: The same ultrasonic cleaning and oxalic acid activation process as in Example 1 was adopted.
[0071] Electroplating solution configuration and process: An electroplating solution of gold, palladium and nickel ions was prepared in a molar ratio of 1.0:0.5:2.0, and no graphene precursor solution was added; the remaining stirring and temperature control parameters remained consistent with those in Example 5.
[0072] The electroplating process uses a periodic reversal pulse power supply with a positive and negative half-cycle current ratio of 1:3, a frequency of 65Hz, and a current density of 0.7A / dm 2 , electroplating time 45 minutes, electroplating solution temperature 55℃.
[0073] Comparative Example 6 (Corresponding to Example 6: Effect of Graphene Doping Concentration on Electrical Properties) Difference and process: Pretreatment and graphene precursor preparation: The same ultrasonic cleaning and oxalic acid activation process as in Example 5 was adopted.
[0074] The graphene precursor concentration was adjusted to 0.05 wt %, and the rest of the preparation processes remained the same.
[0075] Electroplating solution configuration and process: Prepare an electroplating solution of gold, palladium and nickel ions, add 0.05wt% of graphene precursor, and stir evenly to ensure that the graphene is dispersed.
[0076] Electroplating uses a periodic inversion pulse power supply, with a positive and negative half-cycle current ratio of 1:3, a frequency of 65Hz, and a current density of 0.7A / dm 2 , electroplating time 45 minutes, electroplating solution temperature 55℃.
[0077] Experiment 1: Coating surface roughness and glossiness test Experimental Description Purpose: By comparing Example 1, Example 3 and Comparative Example 3, the improvement effect of the pulse current process on the surface roughness and glossiness of the coating is verified, and its mechanism of action in improving the surface quality of the coating is explored.
[0078] Experimental equipment and tools: Surface roughness tester (compliant with ISO 4287-1997, Ra measurement range: 0.01~50μm).
[0079] Gloss meter (60° test angle, in accordance with ISO 2813 standard, gloss range: 0~200GU).
[0080] Coating samples (prepared according to Example 1, Example 3 and Comparative Example 3).
[0081] Experimental steps: Sample preparation: The prepared coating samples were selected from Example 1, Example 3 and Comparative Example 3, respectively, and 3 parallel samples were prepared in each group, marked as A1, A2, A3 (Example 1); B1, B2, B3 (Example 3); C1, C2, C3 (Comparative Example 3).
[0082] Roughness measurement: Place the sample on the platform of the roughness tester, use the stylus to move along the coating surface 3 times, record the Ra value (unit: μm) of each sample, and take the average value of the 3 measurements.
[0083] Gloss measurement: The glossiness of the sample surface was measured at an angle of 60° using a gloss meter. Each sample was measured 3 times, the glossiness value (unit: GU) was recorded, and the average value of the 3 measurements was taken.
[0084] Data recording and analysis: All the measured data were recorded in the experimental table to compare the differences in roughness and gloss between the example and the comparative example samples.
[0085] Experimental data table Table 1: Test data of coating surface roughness and glossiness Sample No. Roughness Ra(μm) Glossiness (GU) A1 0.25 85.3 A2 0.27 87.1 A3 0.26 86.4 B1 0.05 118.6 B2 0.06 119.2 B3 0.07 117.8 C1 0.32 75.2 C2 0.34 76.1 C3 0.33 74.8 Experimental summary and mechanism analysis The experimental results show that the surface roughness of the samples in Example 3 (B1, B2, B3) is significantly reduced, and the Ra value is lower than 0.07μm, while the glossiness is significantly improved, reaching an average of more than 118.5GU. In contrast, the Ra value of the samples in Example 1 (A1, A2, A3) is above 0.25μm, and the glossiness is relatively low (about 86GU on average). The roughness and glossiness of the samples in Comparative Example 3 (C1, C2, C3) are the worst, about 0.33μm and 75GU respectively. The above data fully prove that the pulse current process can significantly improve the surface roughness and glossiness of the coating.
[0086] From a mechanism perspective, the pulse current process (Example 3) adopts a periodic reversal mode during the metal ion deposition process, which promotes the uniform deposition of metal ions through the alternating action of positive and negative currents, reduces the generation of grain boundary defects, and thus significantly reduces the surface roughness (Ra value) of the coating. In contrast, the DC power supply (Example 1 and Comparative Example 3) cannot provide this dynamic control mechanism, resulting in coarse grains and poor surface flatness during the deposition process. In addition, the higher frequency (60Hz) pulse current can also optimize the growth direction of metal grains, improve the surface density of the coating, and make it have higher optical reflectivity, thereby improving glossiness.
[0087] Comparing Example 1 and Comparative Example 3, although Example 1 reduced some roughness by optimizing the cleaning and activation steps, the deposition method of direct current still limited the further improvement of the coating performance. Comparative Example 3 did not adopt the optimized cleaning and activation process, which aggravated the unevenness of grain growth and thus showed the worst roughness and glossiness.
[0088] The experiment verified the superiority of the pulse current process in the present invention, and further explained the importance of the dynamic control mechanism in the metal ion deposition process in improving the surface quality of the coating. This technical improvement not only improves the appearance performance of the coating, but also provides more reliable support for the assembly and use of high-precision electronic components.
[0089] Experiment 2: Coating hardness and wear resistance test Experimental Description Purpose: By comparing Example 1, Example 2 and Comparative Example 2, the enhancement effect of adding molybdenum salt alloying elements on the hardness and wear resistance of the coating is verified, and its mechanism is analyzed from the perspective of microscopic grain structure and alloying effect.
[0090] Experimental equipment and tools: Microhardness tester (conforms to ISO 6507-1 standard, test range: 10~1000HV, test conditions: 0.1kgf load, holding time 10 seconds).
[0091] Wear tester (conforms to ASTM G99 standard, ball-on-disc friction and wear tester, test range: 0.01~50mg).
[0092] Coating samples (prepared according to Example 1, Example 2 and Comparative Example 2).
[0093] Experimental steps: Sample preparation: The prepared coating samples were selected from Example 1, Example 2 and Comparative Example 2, respectively, and 3 parallel samples were prepared in each group, marked as A1, A2, A3 (Example 1); B1, B2, B3 (Example 2); C1, C2, C3 (Comparative Example 2).
[0094] Hardness test: Fix the sample on the platform of the microhardness tester, select the test points (3 random points on the coating surface), apply a load of 0.1 kgf, and hold the load for 10 seconds.
[0095] The diagonal length of the indentation was recorded, the microhardness value (HV) was calculated, and the average of the three measured values was taken.
[0096] Wear resistance test: The ball-on-disc friction and wear test was carried out on a wear testing machine.
[0097] Aluminum oxide balls (diameter 5 mm) were used, a load of 10 N was applied, a sliding speed of 200 rpm, and a friction time of 10 minutes.
[0098] Weigh the sample mass difference (mg) before and after the test and calculate the wear amount.
[0099] Data recording and analysis: The measured hardness and wear amount are recorded in the experimental table, and the hardness and wear resistance performance of the embodiment and the comparative example are compared.
[0100] Experimental data table Table 2: Test data of coating hardness and wear resistance Sample No. Hardness HV Wear amount (mg) A1 210 3.6 A2 205 3.8 A3 215 3.7 B1 250 2.1 B2 260 2.3 B3 255 2.2 C1 195 4.3 C2 190 4.5 C3 200 4.4 Experimental summary and mechanism analysis The experimental results show that the hardness of the samples in Example 2 (B1, B2, B3) is significantly improved, the HV value is more than 250, and the wear amount is significantly reduced (2.2 mg on average). In contrast, the hardness of the samples in Example 1 (A1, A2, A3) is 210 HV on average, and the wear amount is 3.7 mg, while the hardness of the samples in Comparative Example 2 (C1, C2, C3) is the lowest, only 195 HV, and the wear amount is the highest, reaching more than 4.4 mg. The experimental results show that the addition of molybdenum salt alloying elements significantly enhances the hardness and wear resistance of the coating.
[0101] From a mechanistic analysis, the addition of molybdenum salt forms stable intermetallic compounds in the gold-palladium-nickel matrix through alloying. These compounds are distributed in the intergranular gaps of the coating, playing a role in strengthening the grain boundaries, so that the overall hardness of the coating is significantly improved. In addition, molybdenum atoms can further improve the wear resistance of the coating by refining the grain structure. The hardness and wear resistance of Example 2 are significantly better than those of Example 1, thanks to the dual effects of grain refinement and alloy strengthening.
[0102] Comparing Example 1 with Comparative Example 2, it can be seen that even without the addition of molybdenum salt, the optimized process (such as cleaning and activation) can still improve the hardness of the coating to a certain extent (about 8% higher than Comparative Example 2). However, due to the large grains deposited by direct current and the lack of alloying elements, the wear resistance of the coating is poor. Since the sample in Comparative Example 2 has neither the addition of molybdenum salt nor the lack of optimized process, the grains are coarse and the grain boundaries are weakened, so the hardness is the lowest and the wear is the largest.
[0103] It is clear from the experiments that the molybdenum salt alloying design in the present invention is of great significance in significantly improving the hardness and wear resistance of the coating. This improvement lays the foundation for the industrial application of highly wear-resistant electronic connectors, which can significantly extend the service life under high-load environments while reducing maintenance costs. Further optimization of the alloy element ratio can also help achieve a better performance balance.
[0104] Experiment 3: Test of conductivity of coating Experimental Description Purpose: By comparing Example 5 and Example 6 with Comparative Example 5 and Comparative Example 6, the influence of graphene addition and concentration change on the conductive properties of the coating is verified, and its mechanism is analyzed from the perspective of the conductive network structure of the composite material.
[0105] Experimental equipment and tools: Four-probe resistance tester (conforms to ASTM F76 standard, test range 0.1μΩ~200mΩ).
[0106] CNC caliper (used to measure coating thickness, accuracy 0.01mm).
[0107] Coating samples (prepared in Example 5, Example 6, Comparative Example 5 and Comparative Example 6).
[0108] Experimental steps: Sample preparation: Select the prepared coating samples from Example 5, Example 6 and Comparative Example 5, Comparative Example 6, respectively, and prepare 3 parallel samples in each group, marked as: Example 5: E1, E2, E3 Example 6: F1, F2, F3 Comparative Example 5: G1, G2, G3 Comparative Example 6: H1, H2, H3 Thickness measurement: Use a CNC caliper to measure the average thickness of the coating on each sample and record the thickness value (unit: μm).
[0109] Conductivity test: The surface resistance (unit: μΩ / square) of the samples was measured using a four-probe resistance tester. A test point was selected at the center and on both sides of each sample, three test values were recorded, and the average value was taken.
[0110] The volume resistivity is calculated based on the coating thickness, and the conductivity (unit: S / m) is further calculated using the formula: Data recording and analysis: The measured thickness, surface resistance and conductivity were recorded in an experimental table, and the difference in conductivity between different embodiments and comparative examples was analyzed.
[0111] Experimental data table Table 3: Test data of conductive performance of coating Experimental summary and mechanism analysis The experimental results show that the conductivity of samples in Example 6 (F1, F2, and F3) is the best, and the conductivity is more than 2.35×10 7S / m, compared with the conductivity of Example 5 (E1, E2, E3) (about 2.22×10 7 S / m) increased by about 6%, while the conductivity of comparative example 5 (G1, G2, G3) was only 1.98×10 7 The conductivity of samples in comparative example 6 (H1, H2, H3) is slightly improved, but still significantly lower than that of examples 5 and 6.
[0112] From a mechanistic analysis, the addition of graphene can significantly improve the conductivity of the coating, because the unique two-dimensional honeycomb structure of graphene forms an efficient electron transmission network in the coating. In Example 5, the graphene concentration is 0.1wt%, and its distribution has formed a basic conductive network; while in Example 6, the graphene concentration is increased to 0.2wt%, the network is more dense and uniform, and the conductive path is significantly increased, so the conductivity is further improved. However, in Comparative Example 5, without the addition of graphene, the conductive performance of the coating depends only on the gold-palladium-nickel alloy, the electron transmission path is single, and it shows a lower conductivity.
[0113] By comparing Example 6 with Comparative Example 6, it can be found that further optimization of graphene concentration is crucial. In Comparative Example 6, only 0.05 wt% of graphene is added. Due to the uneven distribution of graphene and the difficulty in forming a continuous conductive network, the improvement in conductive performance is limited, and the conductivity is only 2.12×10 7 S / m is significantly lower than that of Example 5 and Example 6. This indicates that when the concentration of graphene is too low, its reinforcing effect cannot be fully exerted.
[0114] Experimental data and mechanism analysis fully demonstrate the technical advantages of the graphene-enhanced coating design in this invention. The optimization of graphene concentration can significantly improve the density and integrity of the conductive network, thereby improving the conductive performance of the coating. This composite material design provides important support for efficient signal transmission of connectors in electronic devices and demonstrates its application potential in extreme environments. By further optimizing the dispersion and doping ratio of graphene, it is expected to achieve better comprehensive performance. Experiment 4: Test of corrosion resistance of coating Experimental Description Purpose: By comparing Example 4 and Example 5 with Comparative Example 4 and Comparative Example 5, the improvement effect of the addition of inhibitors and graphene on the corrosion resistance of the coating is verified, and its mechanism is analyzed from the stability of metal ion deposition and the barrier effect of the composite structure.
[0115] Experimental equipment and tools: Salt spray test chamber (conform to ISO 9227 standard, spray concentration 5%, temperature 35°C).
[0116] Electrochemical tester (using potentiodynamic polarization curve method, in line with ASTM G5 standard).
[0117] Coating samples (prepared in Example 4, Example 5, Comparative Example 4 and Comparative Example 5).
[0118] Experimental steps: Sample preparation: The prepared coating samples were selected from Example 4, Example 5, Comparative Example 4 and Comparative Example 5, respectively, and 3 parallel samples were prepared in each group, which were marked as: Example 4: I1, I2, I3 Example 5: J1, J2, J3 Comparative Example 4: K1, K2, K3 Comparative Example 5: L1, L2, L3 Salt spray test: The samples were placed in a salt spray test chamber and the experimental conditions were set according to ISO 9227 standard: spray concentration was 5%, temperature was 35°C, and test time was 48 hours.
[0119] Check the samples every 12 hours and record the number of corrosion spots and the proportion of corrosion area (expressed as a percentage of the total area) on the sample surface.
[0120] Electrochemical testing: The potentiodynamic polarization curve of the sample in 3.5% NaCl solution was tested using an electrochemical tester.
[0121] Record the corrosion potential (unit: mV) and corrosion current density (unit: μA / cm 2 ) to evaluate the corrosion resistance of the coating.
[0122] Data recording and analysis: The results of the salt spray test and electrochemical test were recorded in the experimental table, and the effects of the inhibitor and graphene on the corrosion resistance were compared and analyzed.
[0123] Experimental data table Table 4: Test data of corrosion resistance of coating Experimental summary and mechanism analysis The experimental results show that the corrosion resistance of samples in Example 5 (J1, J2, J3) is the best, with an average corrosion potential of -206 mV and a corrosion current density of 0.38 μA / cm 2 , which is much better than that of Comparative Example 4 (K1, K2, K3) and Comparative Example 5 (L1, L2, L3), and the number of corrosion spots and the corrosion area are also significantly reduced. The samples of Example 4 (I1, I2, I3) show good corrosion resistance, but are slightly inferior to that of Example 5.
[0124] From a mechanism point of view, the graphene composite coating of Example 5 has an excellent barrier effect, and the two-dimensional structure of graphene forms a dense network in the coating, which can effectively block the penetration of corrosive media (such as water molecules and chloride ions). In addition, the chemical inertness and excellent conductivity of graphene help to reduce the frequency and intensity of electrochemical reactions, thereby significantly improving the corrosion resistance of the coating. In contrast, although the uniformity of metal ion deposition and the density of the coating are improved by the addition of potassium fluoroborate in Example 4, the protective performance of a single metal coating in the face of corrosive media is still not as good as that of a graphene composite structure.
[0125] The experimental results of Comparative Examples 4 and 5 further demonstrate the importance of inhibitors and graphene. In Comparative Example 4, the absence of an inhibitor leads to the inhomogeneity of the grain structure during the deposition process of the plating solution, making it easy for the coating to form pores, significantly reducing the corrosion potential and increasing the corrosion current density. In Comparative Example 5, the lack of the barrier effect of graphene has limited resistance to corrosive media. Although the performance is better than that of Comparative Example 4, it still cannot reach the level of Example 5.
[0126] Experimental data show that the introduction of graphene and the use of inhibitors in the present invention significantly improve the corrosion resistance of the coating, which can meet the long-term use requirements of electronic connectors in extreme environments. This improvement mechanism combines the uniformity optimization of metal deposition and the advantages of graphene composite structure, providing technical support for the development of high-performance anti-corrosion coatings. In the future, by further optimizing the dispersion and doping ratio of graphene, it is expected to achieve more efficient protection effects.
[0127] Experiment 5: Comprehensive performance evaluation of coating Experimental Description Purpose: By comparing Example 1, Example 3, and Example 5 with Comparative Example 1, Comparative Example 3, and Comparative Example 5, the performance of the coating in terms of surface roughness, hardness, and conductivity is comprehensively evaluated, the overall technical advantages of the present invention in multi-dimensional performance improvement are verified, and the reasons for the improvement are analyzed from a mechanistic perspective.
[0128] Experimental equipment and tools: Surface roughness tester (compliant with ISO 4287-1997, Ra measurement range: 0.01~50μm).
[0129] Microhardness tester (conforms to ISO 6507-1 standard, test range 10~1000HV).
[0130] Four-probe resistance tester (conforms to ASTM F76 standard, test range 0.1μΩ~200mΩ).
[0131] Coating samples (prepared by Example 1, Example 3, Example 5 and Comparative Example 1, Comparative Example 3, Comparative Example 5).
[0132] Experimental steps: Sample preparation: Select the prepared coating samples from Example 1, Example 3, Example 5 and Comparative Example 1, Comparative Example 3, Comparative Example 5, respectively, and prepare 3 parallel samples in each group, marked as: Example 1: M1, M2, M3 Example 3: N1, N2, N3 Example 5: O1, O2, O3 Comparative Example 1: P1, P2, P3 Comparative Example 3: Q1, Q2, Q3 Comparative Example 5: R1, R2, R3 Surface roughness test: The roughness of the samples (Ra value, unit: μm) was measured using a surface roughness tester. Each sample was measured 3 times and the average value was taken.
[0133] Hardness test: Use a microhardness tester to randomly select three test points on the sample surface, apply a load of 0.1 kgf, hold the load for 10 seconds, record the hardness value (HV), and take the average value.
[0134] Conductivity test: The surface resistance (unit: μΩ / square) of the samples was measured using a four-probe resistance tester. Each sample was measured 3 times, the average value was taken, and the conductivity (unit: S / m) was calculated.
[0135] Data recording and analysis: All measured data were recorded in an experimental spreadsheet to compare the performance of different samples in terms of roughness, hardness and conductivity.
[0136] Table 5: Comprehensive performance test data of coating Experimental summary and mechanism analysis The experimental results show that the samples of Example 5 (O1, O2, O3) perform best in the three performance indicators, with an average roughness (Ra value) of only 0.04 μm, a hardness of more than 290 HV, and a conductivity of 2.38×10 7S / m. In comparison, the samples of Example 3 (N1, N2, N3) are slightly inferior in roughness and hardness, but still significantly better than Example 1 (M1, M2, M3). The comparative samples performed the worst, among which the roughness and hardness of Comparative Example 1 (P1, P2, P3) and Comparative Example 3 (Q1, Q2, Q3) were lower than those of the example samples, and although some optimization measures were added to Comparative Example 5 (R1, R2, R3), the conductivity and hardness were still lower than those of Example 5.
[0137] From a mechanism perspective, Example 5 forms an efficient two-dimensional conductive network in the coating by introducing graphene, and its barrier effect significantly reduces the diffusion defects of metal ions during the deposition process, thereby improving the surface density and smoothness of the coating. In addition, the high strength and chemical inertness of graphene further enhance the hardness and durability of the coating. In contrast, although Example 3 uses pulsed current technology to optimize the deposition method of metal ions and significantly improves the roughness and hardness, it lacks the auxiliary effect of graphene, and its overall performance is still slightly inferior to Example 5.
[0138] By comparing Example 1 with Comparative Example 1, it can be seen that although Example 1 improves the surface quality and hardness of the coating by optimizing the cleaning and electroplating parameters, the conventional direct current deposition method limits the effect of grain refinement and uniform deposition. Due to the lack of optimization measures, Comparative Example 1 has the highest surface roughness, and the worst hardness and conductivity.
[0139] The experimental results further verified the key innovation of the present invention: the combination of pulse current technology and graphene composite materials can achieve comprehensive optimization in multiple performance indicators. This innovative design not only effectively solves the problems of high coating roughness, low hardness and poor conductivity in the prior art, but also provides a more reliable solution for high-performance electronic connectors and industrial applications in extreme environments. By further optimizing the dispersion ratio of graphene and the pulse current parameters, the performance can be further improved, thereby expanding the application scenarios.
[0140] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for plating gold-palladium-nickel on connector terminals, characterized in that: The following steps are involved: Pretreatment: Clean the connector terminals to be plated to remove grease, dirt and oxide layer, and then activate them by soaking in a weak acid solution to prepare the terminal surface for subsequent deposition; Preparing an electroplating solution: preparing an electroplating solution for generating an alloy phase; Pulse current plating: The pulse current method is used to precipitate metal ions in the plating solution and deposit them on the surface of the connector terminal to form an alloy layer; Electroplating process control: Inhibitors are added during the electroplating process to adjust the pH value and temperature of the plating solution and inhibit the adsorption of impurities; Post-processing: After electroplating, the coating is cleaned and dried, and the appearance quality and various performance indicators of the finished product are checked to ensure that they meet the standards.
2. A method for plating gold-palladium-nickel on connector terminals according to claim 1, characterized in that: The cleaning adopts ultrasonic cleaning technology to remove dirt, and the ultrasonic frequency is 60-80kHz, the cleaning time is 3-10min, the cleaning liquid temperature is 50-60°C, and the ultrasonic power density is 1-2W / cm².
3. A method for plating gold-palladium-nickel on connector terminals according to claim 1, characterized in that: The weak acid solution includes one or more of the following: citric acid solution, oxalic acid solution, phosphoric acid solution and boric acid solution. The soaking time is 1 to 3 minutes, and the surface is immediately cleaned and dried after the soaking.
4. A method for plating gold-palladium-nickel on connector terminals according to claim 1, characterized in that: In the electroplating solution, the molar ratio of gold, palladium and nickel is 0.9-1.1:0.3-0.6:1.8-2.2, and the molar ratio of molybdenum to tungsten is 0.05-0.15:0.85-0.
95.
5. A method for plating gold-palladium-nickel on connector terminals according to claim 1, characterized in that: In the pulse current electroplating, a periodic inversion pulse power supply mode is adopted, and the positive and negative half-cycle current ratio is 0.9-1.1:2.8-3.2, and the frequency is 55-65 Hz.
6. A method for plating gold-palladium-nickel on connector terminals according to claim 1, characterized in that: The inhibitor is potassium fluoroborate, and the pH is maintained in the range of 3.5±0.
1.
7. A method for plating gold-palladium-nickel on connector terminals according to claim 1, characterized in that: The electroplating time is maintained at 45 to 60 minutes, and during electroplating, the temperature of the electroplating solution is maintained at 55 to 60°C.
8. The method for plating gold-palladium-nickel on connector terminals according to claim 1, characterized in that: Graphene-enhanced nanoparticles are further added to the electroplating solution, and the graphene-enhanced nanoparticles are prepared by a sol-gel method. The precursor containing graphene sheets prepared by the sol-gel method is mixed with a gold, palladium, and nickel electroplating solution to form an enhanced plating layer.
Citation Information
Patent Citations
Core-shell structure catalyst for fuel cells and its pulse electrodeposition preparation method
CN103638925A
Continuous production method for preparing multi-layer electrolytic metal terminal by electrolytic treatment production device
CN113322499A